Poetry as cultural practice moral values and social meaning in Malay pantun and Arabic qasida - Ahmad H.Osman, Rahmah; Mohd Yusof, Nurul Syariah; Yaapar, Md. Salleh; Hamawiya Ali, Adham; Che Amran, Aisyah Aminah (Global Academic Excellence, 2025)
Traditional poetic forms have long functioned as vital cultural instruments through which societies articulate moral values, regulate social behaviour, and preserve collective memory. In both Malay and Arab cultures, poetry occupies a central position not merely as an aesthetic expression but as a socially embedded practice that mediates communal relationships and ethical norms. This study offers a comparative analytical examination of pantun in Malay literature and qasida in Arabic literature, focusing on their social and cultural functions within their respective societies. Drawing on qualitative textual analysis and informed by theories of literature as social practice and cultural memory, the study analyses selected pantun and qasida texts to identify patterns of moral instruction, social communication, and identity formation. The findings reveal that despite substantial differences in form, length, and stylistic convention, pantun and qasida perform analogous social roles as vehicles of ethical guidance, communal cohesion, and cultural continuity. While pantun conveys values through metaphorical and indirect expression rooted in Malay ideals of politeness and harmony, qasida articulates moral and cultural authority through rhetorical elaboration and explicit exhortation grounded in Arab historical and religious consciousness. By situating these poetic traditions within a shared analytical framework, the study contributes to comparative literature and cultural studies by demonstrating how culturally distinct literary forms respond to similar social needs and remain relevant in contemporary contexts.